2010
DOI: 10.1073/pnas.1008336107
|View full text |Cite
|
Sign up to set email alerts
|

Observed suppression of ozone formation at extremely high temperatures due to chemical and biophysical feedbacks

Abstract: Ground level ozone concentrations ([O 3 ]) typically show a direct linear relationship with surface air temperature. Three decades of California measurements provide evidence of a statistically significant change in the ozone-temperature slope (Δm O3-T ) under extremely high temperatures (>312 K). This Δm O3-T leads to a plateau or decrease in [O 3 ], reflecting the diminished role of nitrogen oxide sequestration by peroxyacetyl nitrates and reduced biogenic isoprene emissions at high temperatures. Despite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 37 publications
10
143
2
Order By: Relevance
“…The observations in the past three decades demonstrated that October ozone in the SE did not decrease like in July despite anthropogenic emission reductions in the region and that the two October high ozone extremes both occurred in the 2000s, implying higher ozone sensitivity to climate variation in October than July in the region. However, current discussion on the ozone climate penalty (the response of ground-level ozone to climate change) tends to focus on the ozone-temperature relationship (3,4,(6)(7)(8)(9)16). In this study, we find that a significant impact of VPD variation on the climate-chemistry interaction in the SE during the fall.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…The observations in the past three decades demonstrated that October ozone in the SE did not decrease like in July despite anthropogenic emission reductions in the region and that the two October high ozone extremes both occurred in the 2000s, implying higher ozone sensitivity to climate variation in October than July in the region. However, current discussion on the ozone climate penalty (the response of ground-level ozone to climate change) tends to focus on the ozone-temperature relationship (3,4,(6)(7)(8)(9)16). In this study, we find that a significant impact of VPD variation on the climate-chemistry interaction in the SE during the fall.…”
Section: Resultsmentioning
confidence: 48%
“…High ground-level ozone events are typically found in the summer when the formation of ozone is active through photochemical reactions involving nitrogen oxides (NO x = NO + NO 2 ) and volatile organic compounds (VOCs). However, ozone concentrations are sensitive to weather and climate (3)(4)(5)(6)(7)(8), and the high-ozone season could extend beyond summer in the future (9)(10)(11)(12)(13). Previous climate-chemistry model studies have estimated the change of ground-level ozone (ΔO 3 ) in the United States resulting only from meteorological changes.…”
mentioning
confidence: 99%
“…To the north, we may be seeing quicker activated photochemistry with respect to temperature or evidence of suppression of O 3 by high temperatures. This suppression has been identified previously, with one study implicating enhanced PAN decomposition and reduced isoprene emissions (48), and another study finding that the suppression is caused not by temperature-dependent effects on chemistry or emissions, but rather by a breakdown in the linearity of meteorology-O 3 correlations (44). In any case, it is not clear why this relationship changes at 40°N.…”
Section: Resultsmentioning
confidence: 78%
“…By extension, such methods can also provide insight into a model's usefulness for a range of possible (future) environmental conditions. However, care needs to be exercised when employing process-oriented model evaluation approaches because the observed relationships between ozone and the co-measured meteorological field or tracer may be complicated by other competing influences (e.g., Steiner et al, 2010;BrownSteiner et al, 2015;Shen et al, 2016)., or may change over time (e.g., Hassler et al, 2016).…”
Section: Summary Of Evaluation Techniquesmentioning
confidence: 99%